DOES SERVICE INNOVATION IN TOURISM AND HOSPITALITY RELY MORE ON INTERNAL OR EXTERNAL FACTORS? - Lei, Ming; Chen, Chih-Hung (Universitas Negeri Semarang, 2025)
Global tourism is projected to fully recover by 2024, presenting a significant opportunity for the tourism and hospitality industry worldwide. However, companies in this sector continue to face challenges such as a turbulent external environment, high competitiveness, and a lack of confidence in the industry’s recovery. To address these challenges, companies must focus on service innovation and improving their service innovation performance (SIP). Exploring SIP at the individual level is crucial because individual innovation is the foundation of organizational SIP. Based on the resource-based view (RBV), the knowledge-based view (KBV) and contingency theory, this study constructs the research paradigm of